Triangling in Family of Origin, Internet Addiction, and Social Media Addiction: What Is the Role of Experiential Avoidance in the Relationship? - Kurşuncu, Mustafa Alperen; Griffiths, Mark D.; Baştemur, Şule; Şal, Fatih (International Journal of Mental Health & Addiction, 2025)
One of the factors contributing towards a better understanding of social media addiction and internet addiction among university students is family-of-origin experiences. Triangling is one of the factors associated with these online addictions. Moreover, university students with higher experiential avoidance (lower psychological flexibility) may fail to cope with the adverse effects of triangling and develop problematic online behaviors. The present cross-sectional study investigated the mediating role of experiential avoidance in the relationship between triangling, internet addiction, and social media addiction. The sample comprised 839 university students, the majority aged between 18 and 25 years, from more than 50 universities across several regions of Turkey. Participants responded to items in a survey including the Acceptance and Action Questionnaire-II (AAQ-II), Triangular Relationship Inventory (TRI), Bergen Social Media Addiction Scale (BSMAS), Young's Internet Addiction Test-Short Form (YIAT-SF), and a Demographic Information Form. Findings showed that experiential avoidance mediated the association between triangling, social media addiction, and internet addiction. The path of triangling to experiential avoidance to internet addiction to social media addiction explained 65% of the variance. Triangling did not directly contribute to internet addiction and social media addiction unless participants reported experiential avoidance. The present study emphasizes the potential threats associated with triangling on social media addiction and the internet addiction among university students, in which the risks tend to increase as university students use dysfunctional emotional or cognitive coping strategies.